(untitled) (Intent Research Scientific Journal, 2023)
The development of the global Internet system has opened up new prospects for evolutionary improvement in the world education system. Today, traditional teaching methods are being supplemented by new teaching methods based on the Internet, electronic computer sets and telecommunication environment. In addition to performing a number of new functions, tele-education and distance education based on Internet technology require the implementation of specific principles such as the principle of mutually distributed cooperation, integration, access to the international Internet network.